Error Analysis on Learners’ Interlanguage and Intralanguage: A Case Study of Two Adolescent Students - Dian Puspita (Universitas Teknokrat Indonesia, 2019)
This research focuses on exploring learners’ language, especially the errors that are performed by the English learners. The subjects of this study are two adolescent students who have been learning English since early age. The data analyzed is collected by doing the interview session. Identification and classification are done toward the errors performed by the subjects. After that, the pattern is drawn to find out the subjects’ nature of language. The result shows that both interlanguage and intralanguage affect the students’ English. However, interlanguage affects the errors more than does intralanguage. It proves that the nature of L1 affects the L2 acquisition. The errors occurred in terms of subject-verb agreement, tenses, and relative clause. At the end, the appropriate feedback given to speaking performance is implicit correction such as recast and prompts.Keywords: Error analysis, feedback, intralanguage, interlanguage